CHARACTERIZATION OF THE OVERPRODUCTION RESULTS AND PURIFICATION OF RECOMBINANT CATALASE HYDROPEROXIDASE II ENZYME IN ESCHERICHIA COLI BL21(DE3) - Anandita Shandyakiran, Keisha
Catalase is one of antioxidant enzymes with its role catalysing the reduction reaction of hydrogen peroxide into oxygen and water. Catalase hydroperoxidase II (HPII) is one of the monofunctional catalases that does not have peroxidase activity. This study aims to characterize the product of the overproduction process of recombinant HPII catalase enzyme in Escherichia coli BL21 (DE3) based on a research procedure at Biotechnology Laboratory of the School of Pharmacy ITB, and perform purification to the protein. E. coli BL21(DE3) bacteria had previously inserted with a plasmid carrying the HPII catalase gene. The overproduction was carried out by co-expression of the pG-Tf2 chaperone system to increase protein solubility. Purification was performed by Ni-NTA affinity chromatography and ammonium sulphate precipitation with a saturation range of 30-70%. Catalase activity was measured by bubble assay and colorimetric assay. The overproduction system produced soluble HPII catalase, cell pellet weight, and total protein of 0.27 - 2.51 mg, 1.1 - 1.89 g, and 24.8 - 56.1 mg/mL, respectively. Whereas with the co-expression of chaperone pG-Tf2, the soluble catalase, cell pellet weight, and total protein were 1.75 - 7.35 mg, 1.35 - 1.43 g, and 35.5 - 96.6 mg/mL. Ni-NTA affinity column could not purify HPII catalase in this study. Ammonium sulphate precipitation succeeded in reducing proteins other than HPII even though not completely (partially purified). The greatest catalase activity was found at 50% ammonium sulphate saturation for overproduction without chaperone co-expression and at 40% saturation for chaperone coexpression. The chaperone co-expression system was found reduced the catalase activity of HPII.